To what extent do structural quality indicators of (nutritional) care influence malnutrition prevalence in nursing homes?. Issue 6 (December 2015) - van Nie-Visser, Noémi C.; Meijers, Judith M.; Schols, Jos M.; Lohrmann, Christa; Spreeuwenberg, Marieke; Halfens, Ruud J.
Summary: Background & aims: Many residents in European healthcare institutions are malnourished, with reported malnutrition prevalence rates of up to 60%. Due to the negative effects of malnutrition it is important to optimize the quality of nutritional care. If structural quality indicators of nutritional care might improve resident care and outcome is not yet known. The aim of this study is to explore whether structural quality indicators for nutritional care influence malnutrition prevalence in Dutch, German and Austrian nursing homes. Methods: This study follows a cross-sectional, multi-center design. Data were collected by using a standardised questionnaire at resident, ward and institution level. Results: Data from 214 nursing homes (NL = 133, G = 61, A = 20) were analysed. The prevalence of malnutrition varied significantly between the three countries (NL = 18.2% G = 20.1% A = 22.5%). Two structural quality indicators at ward level namely (1) the policy that the care file should include the nutritional intake for each patient and (2) having a weight measurement policy at ward level are predictive for malnutrition prevalence. Furthermore also the variable country was of influence. Conclusions: A policy of registering nutritional intake in the file of the patient and a policy to assess the patient's weight regularly have a positive influence on malnutrition prevalence.